Neutrophil extracellular traps in nasal secretions of patients with stable and exacerbated chronic rhinosinusitis and their contribution to induce chemokine secretion and strengthen the epithelial barrier. Issue 10 (12th July 2019) - Hwang, Jae Woong; Kim, Jae Hyung; Kim, Hyun Jung; Choi, In Hak; Han, Hye Min; Lee, Ki Jung; Kim, Tae Hoon; Lee, Sang Hag
Abstract: Background: Neutrophil extracellular traps (NETs) participate in innate immunity by trapping microorganisms. Their pathophysiological implications have not been defined in chronic rhinosinusitis (CRS). Objective: We investigated the presence of NETs in nasal secretion of patients with stable or exacerbated CRS and evaluated whether NETs participate in the secretion of chemokines in sinonasal epithelial cells, the epithelial permeability, and transendothelial leucocyte migration, and elucidate whether NETs are released by macrolides and dexamethasone. Methods: The presence of NETs in nasal secretion and the release of NETs from neutrophils stimulated with macrolides or dexamethasone were evaluated by dsDNA Assay kit and fluorescence microscope. The chemokine secretion, epithelial permeability, and transendothelial leucocyte migration were measured in cultured cells incubated with NETs, the supernatant of unstimulated neutrophils (unstim), NETs inhibitor (DPI), or H3Cit, where the expression of junctional complex proteins and ICAM‐1 was evaluated by real‐time PCR, Western blots, and confocal microscope. Results: The amount of NETs and NETs‐forming neutrophils in nasal secretion increased in exacerbated CRS. Epithelial cells treated with NETs or H3Cit secreted chemokines and showed decreased permeability associated with up‐regulated junctional complex proteins. Increased transendothelial leucocyte migration associated with up‐regulated ICAM‐1 was noted in endothelial cells treated with NETs or H3Cit. These findings were not found in cells treated with unstim, or DPI. NETs were released by macrolides, but not by dexamethasone. Conclusions and Clinical Relevance: NETs formation increased in exacerbated CRS, inducing chemokine secretion, strengthening the epithelial barrier, and promoting the neutrophils infiltration. Therefore, the release of NETs in CRS might be beneficial or detrimental to CRS patients.